2019
DOI: 10.21070/jees.v4i2.2443
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Essay Writing Using Authentic Materials to Improve Students' Writing Performance

Abstract: This study used authentic material as the tool in essay writing class. Authentic material is made not for teaching need; it is the material that bring real language knowledge. It can be brought to the class as a learning tool. There two beneficial types of authentic materials; printed and audio authentic materials. This research used authentic printed materials to improve students' writing achievement. This is a Classroom Action Research in three cycles. This study aims to explain in detail the implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It was concluded that the use of authentic material was effective in improving students' abilities in making procedural texts. Recent research has also revealed that authentic material is effective in improving students' ability to write essays (El-Sulukiyyah & Aisyah, 2019). Furthermore, through experimental design carried out at a university in Ecuador, Chamba, Reinoso, Rengifo (2019) have also proven that students who use authentic material are able to write better in terms of coherence, cohesion, use of vocabulary, grammar, and also in cultural understanding.…”
Section: Introductionmentioning
confidence: 97%
“…It was concluded that the use of authentic material was effective in improving students' abilities in making procedural texts. Recent research has also revealed that authentic material is effective in improving students' ability to write essays (El-Sulukiyyah & Aisyah, 2019). Furthermore, through experimental design carried out at a university in Ecuador, Chamba, Reinoso, Rengifo (2019) have also proven that students who use authentic material are able to write better in terms of coherence, cohesion, use of vocabulary, grammar, and also in cultural understanding.…”
Section: Introductionmentioning
confidence: 97%
“…Through writing, students can refine their concepts and strengthen students' language competencies so they can be expressed in written performance (Elsulukiyyah and Aisyah, 2019). Ali et al (2021) concluded that non-native speakers have problems in terms of ideas generation, technical aspects of essay writing, and limited vocabulary mastery.…”
Section: Introductionmentioning
confidence: 99%
“…According to Elsulukiyyah and Aisyah (2019), there are two approaches to teaching essays; writing as a process and writing as a product. When students write as products, they do so based on assigned topics without the guidance or advice of their teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Realia is expected to be one of the teaching tools for descriptive text. It is a plastic replica object that students can use to express and develop their ideas (El Sulukiyyah & Aisyah, 2019). Realia can assist students in recognizing an object or a person by assisting them with the shape, characteristic, taste, or smell, allowing them to write about their ideas more easily.…”
Section: Introductionmentioning
confidence: 99%